A multi-metabolite signature robustly predicts long-term mortality in the PREDIMED trial and several US cohorts - Fernández-Duval, Gonzalo; Razquin, Cristina; Wang, Fenglei; Yun, Huan; Hu, Jie; Guasch-Ferré, Marta; Rexrode, Kathryn; Balasubramanian, Raji; García-Gavilán, Jesús F; Ruiz-Canela, Miguel; Clish, Clary B; Corella, Dolores; et al. (Elsevier, 2025)
Metabolome-based biomarkers contribute to identify mechanisms of disease and to a better understanding of overall mortality. In a long-term follow-up subsample (n = 1878) of the PREDIMED trial, among 337 candidate baseline plasma metabolites repeatedly assessed at baseline and after 1 year, 38 plasma metabolites were identified as predictors of all-cause mortality. Gamma-amino-butyric acid (GABA), homoarginine, serine, creatine, 1-methylnicotinamide and a set of sphingomyelins, plasmalogens, phosphatidylethanolamines and cholesterol esters were inversely associated with all-cause mortality, whereas plasma dimethylguanidino valeric acid (DMGV), choline, short and long-chain acylcarnitines, 4-acetamidobutanoate, pseudouridine, 7-methylguanine, N6-acetyllysine, phenylacetylglutamine and creatinine were associated with higher mortality. The multimetabolite signature created as a linear combination of these selected metabolites, also showed a strong association with all-cause mortality using plasma samples collected at 1-year follow-up in PREDIMED. This association was subsequently confirmed in 4 independent American cohorts, validating the signature as a consistent predictor of all-cause mortality across diverse populations.
Keywords: Metabolitos; Biomarkers; Plasma metabolites; Metabolomic; Metabolomic signature; All-cause mortality